Innovative Multi-Actor Collaborations as Collective Actors and Institutionalized Spaces. The Case of Food Governance Transformation in Leuven (Belgium) - Medina-García, Clara; Nagarajan, Sharmada; Castillo-Vysokolan, Lariza; Béatse, Erik; Van den Broeck, Pieter (Frontiers in Sustainable Food Systems, 2022)
The sustainable transformation of food systems is a particularly prolific field in which innovative multi-actor collaborations (IMACs) are being tested. Despite the growing literature on food governance and transformation of food systems, and on the principles of alternative food networks and local food strategies, little is known about how these are implemented and how multi-actor networks are coordinated and governed. Taking food as a lens, our objectives are to identify (1) how IMACs are established, (2) how collaboration is enacted within them, and (3) how governance innovations in these fields affect and are affected by broader urban governance innovation. Methodologically, we take a transdisciplinary action research approach, combining different groups of researchers with stakeholders involved in two on-going and interacting IMAC trajectories in Leuven (Belgium), i.e., the non-profit governmental organization Leuven2030 aiming to achieve climate-neutrality and the parallel collective development and implementation of the local food strategy “Food Connects.” After reconstructing the trajectory of these IMACs from a governance perspective and discussing their current limitations, we realize that these IMACs perform both as collective actors and as institutionalized spaces for experimentation and transformative change. Our findings demonstrate that IMACs can be an empowering tool for local actors to challenge supra-local and systemic power imbalance and injustice; that networking and supra-local connections of urban actors can increase the legitimacy and outreach of transition processes, mobilization of resources and peer-learning; and that the consolidation of IMACs builds on previous sedimentations of experimentation and benefits from the impulse of political will in specific windows of opportunity. We conclude that the institutionalization of common objectives set within IMACs requires a parallel institutionalization of governance structures that enabled reaching them, which entails defining specific roles and responsibilities among actors and ensuring stable spaces for conflict, deliberation, and negotiation.